2017
DOI: 10.1007/s00261-017-1130-7
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of MR defecography in the evaluation of pelvic floor dysfunction: our experience using 3T MRI

Abstract: MR defecography is the modality of choice in assessing pelvic floor dysfunction, because it can neatly show various pelvic organ abnormalities from all compartments in a dynamic fashion, which are frequently coexistent. It can even show clinically silent or unsuspected abnormalities which can impact the management of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Prolapse assessment using the POP‐Q confirmed a significant posterior compartment bulge (Ap: −2, Bp: 0). Magnetic resonance defecography reported mild vaginal prolapse (1.7 cm), a moderate cystocele (3.2 cm), a moderate enterocele (5.7 cm), and a moderate rectocele with distal bulge (1.2 cm) along the posterior vaginal wall. Rectal intussusception was also noted with partial thickness mucosal invagination, full‐thickness invagination of the posterior wall of the rectum, and partial anterior wall invagination (Fig.…”
Section: Case Presentationmentioning
confidence: 99%
“…Prolapse assessment using the POP‐Q confirmed a significant posterior compartment bulge (Ap: −2, Bp: 0). Magnetic resonance defecography reported mild vaginal prolapse (1.7 cm), a moderate cystocele (3.2 cm), a moderate enterocele (5.7 cm), and a moderate rectocele with distal bulge (1.2 cm) along the posterior vaginal wall. Rectal intussusception was also noted with partial thickness mucosal invagination, full‐thickness invagination of the posterior wall of the rectum, and partial anterior wall invagination (Fig.…”
Section: Case Presentationmentioning
confidence: 99%
“…Thus MR defecography is beneficial in detecting or differentiating cases of enteroceles in apical or posterior compartment prolapse [34]. Additional utility of MR defecography lies in its ability to demonstrate associated pelvic floor abnormalities in multiple compartments in addition to the expected clinical diagnoses [35,36].…”
Section: Initial Imagingmentioning
confidence: 99%
“…MR defecography can also add clinical benefit in patients with rectal disorders by revealing additional clinically occult abnormalities such as enteroceles that alter patient management [35,87,88]. A study by Rentsch et al [36] demonstrated that, in patients with posterior compartment symptoms and defecatory dysfunction, MR defecography demonstrated multifocal defects in a significant number of patients and revealed defects in addition to clinical diagnoses in 34% of cases.…”
Section: Fluoroscopymentioning
confidence: 99%